UCAmI 2018 2018
DOI: 10.3390/proceedings2191225
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Recognition of Interleaved Activities Based on Ensemble Classifier of Long Short-Term Memory with Fuzzy Temporal Windows

Abstract: In this paper, we present a methodology for Real-Time Activity Recognition of Interleaved Activities based on Fuzzy Logic and Recurrent Neural Networks. Firstly, we propose a representation of binary-sensor activations based on multiple Fuzzy Temporal Windows. Secondly, an ensemble of activity-based classifiers for balanced training and selection of relevant sensors is proposed. Each classifier is configured as a Long Short-Term Memory with self-reliant detection of interleaved activities. The proposed approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…To generate the input datasets by preprocessing the raw sensor data, multiple and incremental fuzzy temporal windows (FTW) are used. FTW is used as a successful technique to segment the sensor data and prepare the input datasets [4,6,9,18,57]. FTW has shown that it can capture signal sensors of a long and short duration of human activities such as sleep or snack from raw sensor data [4,57].…”
Section: Preprocessing Smart Home Datamentioning
confidence: 99%
“…To generate the input datasets by preprocessing the raw sensor data, multiple and incremental fuzzy temporal windows (FTW) are used. FTW is used as a successful technique to segment the sensor data and prepare the input datasets [4,6,9,18,57]. FTW has shown that it can capture signal sensors of a long and short duration of human activities such as sleep or snack from raw sensor data [4,57].…”
Section: Preprocessing Smart Home Datamentioning
confidence: 99%
“…To develop intelligent systems from sensor data streams, a new approach was introduced for online AR with three temporal sub-windows [50][51]. Moreover, an ensemble of activity-based classifiers was presented for balanced training and the selection of relevant sensors using FTWs [52]. Even though the fuzzy temporal feature extraction-based approaches in [47][48][49][50][51][52] exhibited advanced performance, performance degradation owing to the unlabeled data for other activities that comprise half of the dataset and present high correlation to the labeled data were not investigated.…”
Section: A Temporal Dependency-based Feature Extractionmentioning
confidence: 99%
“…However, long-term historical data are significantly vast, for example, several hours or a day before query time, and they should be compressed and transformed into a single feature matrix to be effectively learned. In this study, fuzzy features extracted by fuzzy temporal windows (FTWs) [47][48][49][50][51][52], which is a data representation method that effectively compresses large preceding data, were used.…”
Section: Introductionmentioning
confidence: 99%
“…An ensemble of long short-term memory (LSTM) with fuzzy temporal windows method was proposed to solve real-time recognition of interleaved activities in [37]. The authors proposed a representation of binary-sensor activations based on multiple fuzzy temporal windows and then trained an ensemble of LSTM [38] classifiers.…”
Section: Related Workmentioning
confidence: 99%